2010
DOI: 10.1186/1471-2474-11-233
|View full text |Cite
|
Sign up to set email alerts
|

Walking ability during daily life in patients with osteoarthritis of the knee or the hip and lumbar spinal stenosis: a cross sectional study

Abstract: BackgroundDegenerative musculoskeletal disorders are among the most frequent diseases occurring in adulthood, often impairing patients' functional mobility and physical activity. The aim of the present study was to investigate and compare the impact of three frequent degenerative musculoskeletal disorders -- knee osteoarthritis (knee OA), hip osteoarthritis (hip OA) and lumbar spinal stenosis (LSS) -- on patients' walking ability.MethodsThe study included 120 participants, with 30 in each patient group and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 17 publications
7
86
0
8
Order By: Relevance
“…This same study af irms that diabetes has a greater in luence on disability than hypertension. Winter et al (30) observed that individuals with osteoarticular diseases have less mobility than their healthy peers. In this study none of the investigated diseases (hypertension, diabetes and osteoarticular diseases) were associated with the mobility of the oldest old.…”
Section: Discussionmentioning
confidence: 99%
“…This same study af irms that diabetes has a greater in luence on disability than hypertension. Winter et al (30) observed that individuals with osteoarticular diseases have less mobility than their healthy peers. In this study none of the investigated diseases (hypertension, diabetes and osteoarticular diseases) were associated with the mobility of the oldest old.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of imaging methods and the increased aging of society, the incidence of LSS has shown an annual increase. LSS is one of the main causes of leg pain in older individuals (1)(2)(3)(4), including intermittent claudication, numbness of buttocks and legs, activity disorder of waist and legs, muscle wasting and tendon dysreflexia (5). Intermittent claudication caused by neuropathic pain (NP) is a special chief complaint of LSS, which may be reconstructed by clinical workers; however, its mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar spinal stenosis is characterized by neurogenic claudication and mobility limitations [1][2][3]17,18]. Yet, despite the fact that neurogenic claudication is the hallmark of LSS, the effects of symptoms on free-living physical activity (performance) are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, recent advances in wearable technology have provided us with the tools to objectively measure free-living physical activity (performance) in people with LSS. Using accelerometers, we are beginning to understand more about performance in this population [1][2][3]20,21]. Some preliminary work with pedometers demonstrated that people with LSS take an average of around 4,000 steps/day [17], which is considered sedentary [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation